Effect of AlN content on the lattice site location of terbium ions in AlxGa1−xN compounds. (22nd February 2016) - Fialho, M; Rodrigues, J; Magalhães, S; Correia, M R; Monteiro, T; Lorenz, K; Alves, E
Abstract: Terbium lattice site location and optical emission in Tb implanted Al x Ga1− x N (0 ≤  x  ≤ 1) samples grown by halide vapour phase epitaxy on (0001) sapphire substrates are investigated as a function of AlN content. The samples were implanted with a fluence of 5 × 10 14 cm −2 of terbium ions and an energy of 150 keV. Lattice implantation damage is reduced using channelled ion implantation performed along the 〈0001〉 axis, normal to the sample surface. Afterwards, thermal annealing treatments at 1400 °C for GaN and 1200 °C for samples with x  > 0 were performed to reduce the damage and to activate the optical emission of Tb 3+ ions. The study of lattice site location is achieved measuring detailed angular ion channelling scans across the 〈0001〉, and axial directions. The precise location of the implanted Tb ions is obtained by combining the information of these angular scans with simulations using the Monte Carlo code FLUX. In addition to a Ga/Al substitutional fraction and a random fraction, a fraction of Tb ions occupying a site displaced by 0.2 Å along c- axis from the Ga/Al substitutional site was considered, giving a good agreement between the experimental results and the simulation. Photoluminescence studies proved the optical activation of Tb 3+ after thermal annealing and the enhancement of the 5 D4 to 7 F6 transition intensity with increasing AlN content.